PATTERNS AND CONDITIONS OF DEFORMATION IN THE PLATTENKALK NAPPE , CRETE , GREECE : A PRELIMINARY STUDY - Fassoulas, C.; Rahl, J. M.; Ague, J.; Henderson, K. (Bulletin of the Geological Society of Greece, 2004)
We present preliminary results from an ongoing study of deformation and fluid flow within the meta-carbonates of the Plattenkalk nappe exposed in central and western Crete, Greece. Deformation was controlled by lithological properties and is mainly expressed as makro- to meso-scale folds and localized thrusts. Folds along several profiles are mainly asymmetric flexural-slip folds with south to southeast vergence, sub-horizontal east-west trending fold axes, and variable fold opening angles. The large folds commonly invert the stratigraphie section. Variable recrystallization near cracks and bedding contacts within the carbonate rocks suggests that localization of fluids into channelways left much of the rock sequence "dry" during metamorphism. The style of the late Tertiary deformation and general tectonic setting for the Plattenkalk nappe suggests that accretion and deformation are "thin-skinned".